Vasorelaxant effects of 3,5,7,3',4'-pentamethoxyflavone isolated from Kaempferia parviflora: partly stimulating the release of NO and H2S by rat thoracic aorta - Yorsin, Somruedee; Sukpondma, Yauwapa; Jansakul, Chaweewan (Journal of Physiological and Biomedical Sciences, 2015)
Pentamethoxyflavone (PMF) was isolated from the rhizomes of Kaempferia parviflora, a plant that is claimed to have anti-hypertensive effects. We have investigated the activity of the PMF on isolated rat thoracic aortic rings. PMF caused a relaxation of phenylephrine precontracted aortic rings, and this effect was inhibited by NG-nitro-L-arginine (LNA), ODQ (guanylyl cyclase inhibitor), or by removal of the vascular endothelium. In the presence of LNA or removal of the endothelium, ODQ potentiated the relaxant activity of the PMF, and this effect was inhibited by DL-propargylglycine (PAG, a cystathionine-γ-lyase inhibitor) and SQ22536 (an adenylyl cyclase inhibitor). Glybenclamide, but not tetraethylammonium, potentiated the relaxation of the PMF whether LNA was present or not, and the potentiation was inhibited by PAG and SQ22536. In normal Krebs solution with nifedipine, or in a Ca2+-free Krebs solution, PMF caused a further inhibition of the phenylephrine concentration- response (C-R) curve of the aortic ring. In the aortic ring treated with thapsigargin, PMF suppressed the phenylephrine C-R curve and a further suppression was found when nifedipine, SKF-96365 (store-operated Ca2+ channel inhibitor) and/or Y-27632 (Rho-kinase inhibitor) was also added. These results revealed that PMF caused a relaxation of thoracic aortic rings by stimulating the release of nitric oxide and H2S, that act as an adenylyl cyclase stimulator, and an inhibitor of intracellular calcium mobilization.